Novel ZnO–ZnS nanowire arrays with heterostructures and enhanced photocatalytic properties1. Issue 33 (7th September 2015) - Gao, Xingxing; Wang, Jian; Yu, Jianglong; Xu, Hongbo
<x xml:space="preserve">Abstract</x> The graphical abstract exhibits the SEM images and schematic representation of ZnO–ZnS heterostructure NW arrays, the schematic energy band diagram and the rates of the photocatalytic H2 at different temperatures.